Nano-size ceramic reinforced 3D biopolymer scaffolds: Tribomechanical testing and stem cell activity. (15th October 2018) - Shishkovsky, Igor; Sherbakov, Vladimir; Ibatullin, Ildar; Volchkov, Vladislav; Volova, Larisa
Abstract: The present study was aimed to study the nanosize ceramic reinforced 3D biopolymer scaffolds on the stem cells viability, proliferative activity, and phenotypic changes during the testing. We used the biocompatible polymer (polyetheretherketone – PEEK) and determined the optimal regimes of the laser powder bed fusion process. The powders of biocompatible nano-size reinforced oxide ceramics – TiO2, Al2 O3, ZrO2, and hydroxyapatite were carried out as a basis of the additives. The influence of additional heating during PBF process on the mechanical and tribological properties and stem cell behavior near ceramoplastic scaffolds reinforced by nano oxide's inclusions were carried out.